The Implications of the New Silk Road Railways on Local Development - Ling Fang; Martin Kleimann; Yuan Li; Hans-Jörg Schmerer (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies regional treatment effects of infrastructure projects on economic growth, employment and intermodal transport volumes. The recent Belt and Road Initiative provides an experiment that can be evaluated using matching econometrics. Our results show that the establishment of a new railway connection is not systematically associated with short-run economic growth. However, it spurs employment and road freight by stimulating intermodal transport.
Keywords: F00; F15; F19; 330; infrastructure; development; trade